Development of Learning Media Based on Autoplay Chemistry to Improve Students’ Communicative Characters on Chemistry - Maria Erna; Irfandi Irfandi; Rasmiwetti Rasmiwetti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2020)
The implementation of learning media based on ICT (Information and Communication Technology) on chemistry was found to be very low. For this reason, ICT-based chemistry learning media which utilized autoplay application were developed in this research. The validated product of the learning media based by autoplay on chemistry can be implemented as a learning medium to improve students' communicative character. This research was designed by using the Plomp model in the form of Research and Development (R&D). Data of this research were collected by validation sheets, questionnaire responses (teachers and students), and communicative observation sheets with descriptive statistical analyses and independent sample t test. The validity results showed that the average percentage from media expert and material expert judgment were 88.25% and 91.69% with a category of valid. Moreover, the results of the response of teachers and students respectively obtained an average percentage score of 85% and 81% with a category of very interesting. Then, the results of the independent sample t test for 0,000 <0.05 indicated that there were significant differences in the communicative character of students before and after the use of learning media based on autoplay on chemistry with a percentage of 72.25%.